Walter Rodney and the Unclaimed Past: Sierra Leone Historiography’s Refusal of a Radical Inheritance: CODESRIA Bulletin Online, No. 5, June 2026 - Ibrahim Abdullah (CODESRIA Bulletin, 2026)
Walter Rodney occupies a strange place in the historiography of Sierra Leone. He is everywhere and nowhere. His work shadows some of the most important questions that can be asked about Sierra Leone’s past, yet he has rarely been placed at the centre of Sierra Leonean historical reflection. His presence is foundational, but his reception has been faint. He gave historians one of the most powerful frameworks for understanding the deep past of the region that became Sierra Leone, yet that framework has been neither fully absorbed nor systematically challenged by Sierra Leonean scholars. It has, in many respects, been bypassed. This is more than an omission. It is a refusal. Rodney’s doctoral dissertation, later published as A History of the Upper Guinea Coast, 1545– 1800, was not a narrow local study, nor was it merely a contribution to the precolonial history of a coastal zone. It was an intervention into how African history should be written. Its geographical field stretched across the Upper Guinea Coast, from the Gambia down towards Cape Mount, and within that space Sierra Leone was not marginal. It was central to the historical processes Rodney was reconstructing: migration, warfare, political formation, trade, slavery, social stratification, African agency and the long violence of Atlantic incorporation. Rodney did not begin Sierra Leone’s history with Freetown. He did not begin with British humanitarianism, the Province of Freedom, the Nova Scotians, the Maroons, the Liberated Africans, Fourah Bay College, missionary education or the colonial state. He began before the colonial archive had established the boundaries of the thinkable. He began with African societies in motion, with the Mani invasions, with the encounter between coastal communities and incoming military-political forces, with older structures of power and production, and with the gradual intrusion of European commerce into already dynamic African historical worlds. That choice alone marks him as a major figure in Sierra Leone historiography. For if Sierra Leonean history is allowed to begin only with Freetown, then the country’s past is already colonised before the historian begins to write. The categories are inherited from empire: colony and protectorate; settler and native; Creole and provincial; civilised and customary; Christian and pagan; British order and African disorder. Rodney’s work broke that frame. He insisted that the territory later called Sierra Leone had histories before Sierra Leone; that its peoples were not waiting for incorporation into the British Empire in order to become historical; that the Atlantic world entered a region already marked by political experiment, violence, exchange, hierarchy and struggle. His treatment of the Mani invasions is one of the most important examples of this method. For Rodney, the Mani were not simply an ethnic origin story or a convenient explanation for later cultural formations. They were a historical problem through which one could examine conquest, class formation, military innovation, political consolidation, social reorganisation and the making of new ruling groups. The Mani invasion was not folklore to be domesticated into identity. It was a window into power. That is what made Rodney’s work so different. He was not content with listing events. He wanted to know what those events did to society. Who ruled? Who laboured? Who fought? Who was captured? Who traded? Who accumulated? Who mediated between African communities and foreign merchants? Who lost autonomy? Who gained power? What forms of exploitation predated European rule, and how were they transformed by the Atlantic slave trade? These were not antiquarian questions. They were questions about the making and remaking of social relations. This is why Rodney must be placed at the centre of a people-centred historiography of Sierra Leone, even if he has not been institutionally recognised as such. His interest was not in rulers alone, nor in ethnic origins as static inheritances, nor in colonial institutions as the natural containers of history. He was interested in social formations. He wanted to understand how communities produced, exchanged, fought, ruled, absorbed outsiders, generated dependents and responded to the pressures of long-distance trade. His was a history of ordinary people, but not in a sentimental sense. He did not romanticise ‘the people’ as an innocent mass outside history. He placed them within structures of production, violence, domination and resistance. That was what made his historiography combative. Its combativeness was not a matter of rhetorical aggression. It came from its emancipatory intent. Rodney wrote African history against the imperial archive, against colonial common sense and against the idea that Europe was the author of African historical movement. But he also wrote against simple nationalist consolation. He did not merely replace European heroes with African heroes. He asked harder questions. He asked how African ruling classes participated in the slave trade. He asked how external demand changed internal hierarchies. He asked how African sovereignty could coexist with growing dependency. He asked how societies could retain agency while being drawn into an unequal world system. That tension is crucial. Rodney’s work cannot be reduced to a story in which Europe acts and Africa suffers. Nor can it be reduced to a nationalist story in which African agency is invoked to avoid discussing exploitation. His Upper Guinea history held both truths together: African societies were active makers of history, and they were increasingly incorporated into a global system whose terms were set elsewhere. This is what made his work so useful for understanding Sierra Leone. The region was neither a passive victim nor a sovereign island. It was a historical field in which local power and external capitalism became entangled. The link between A History of the Upper Guinea Coast and How Europe Underdeveloped Africa is therefore not incidental. The later book did not emerge from nowhere. It was not a slogan pasted onto African history from outside. It was the theoretical and political expansion of questions Rodney had already explored in the Upper Guinea material. The dissertation gave him the concrete historical anatomy: coastal trade, slave raiding, brokerage, ruling groups, European merchants, African intermediaries, shifting forms of production and the social consequences of external demand. How Europe Underdeveloped Africa turned that anatomy into a continental and world-historical argument. In that classic text, Rodney linked the historical study of Africa to the contemporary struggles of the Third World. He argued that underdevelopment was not a natural condition, not a cultural failure, not the result of African isolation from history, but a product of historical relations. Europe developed through the same process by which Africa was underdeveloped. That argument was sharpened by his earlier work. Sierra Leone and the Upper Guinea Coast were not merely examples that illustrated a theory formed elsewhere. They were part of the ground from which the theory grew. This is why Rodney matters so profoundly to Sierra Leone historiography. He allows us to connect the ‘precolonial’, the ‘colonial’ and the ‘postcolonial’ without treating them as sealed compartments. He gives us a way to think from the Mani invasions to the Atlantic slave trade, from coastal brokerage to British colonialism, from ‘legitimate commerce’ to mineral extraction, from colonial infrastructure to postcolonial dependency, from local ruling classes to global capitalism. He enables a history of Sierra Leone that is not trapped inside the nation-state but also not dissolved into abstraction. He makes Sierra Leone visible as a place where world history touched ground. And yet, this inheritance has not been properly claimed. No Sierra Leonean scholar has meaningfully built a sustained historiographical project around Rodney’s findings. His work is cited, perhaps, but not wrestled with. It is acknowledged, sometimes, but not made generative. The Mani debate continued, but often without taking the full measure of Rodney’s social and political interpretation. Studies of the colony and protectorate continued, but often without integrating Rodney’s longue durée of Upper Guinea historical formation. Discussions of underdevelopment, dependency and postcolonial failure proceeded, but often without returning to the deep structures Rodney identified in the earlier history of Atlantic incorporation. His contribution has been dwarfed, neglected or treated as external to the Sierra Leonean historical canon. This neglect is revealing. Sierra Leone historiography has often been organised around certain familiar axes: the founding of Freetown, the emergence of Creole society, missionary education, colonial administration, the Hut Tax War, paramount chiefs, party politics, diamonds, civil war, corruption and state collapse. These are important themes. But they can produce a fragmented history if they are not connected to deeper structures. Rodney’s work offered precisely such a connection. He showed that Sierra Leone’s past must be understood through the making of social relations over time: the relation between coast and interior, trade and violence, slavery and production, African ruling groups and foreign capital, colonial power and local intermediaries, underdevelopment and resistance. The refusal to engage with Rodney is therefore not simply a gap in scholarship. It is a symptom of a larger problem: the weakness of a radical Sierra Leonean historiography capable of linking historical knowledge to emancipatory politics. Rodney’s work was dangerous because it refused innocence. It denied Europe the innocence of civilisation. It denied colonialism the innocence of order. It denied African elites the innocence of victimhood. It denied nationalism the comfort of shallow origins. It insisted that history must expose the structures through which power is made, wealth is extracted and people are subordinated. That may be one reason he has remained unclaimed. Rodney’s historiography demands too much. It demands that Sierra Leonean historians look beyond institutional respectability and ask unsettling questions about class, exploitation, dependency and betrayal. It demands that the history of the protectorate be linked to older histories of coercion and accumulation. It demands that the history of Freetown be read not only as a story of liberation but also as a story of imperial humanitarianism, labour discipline, cultural hierarchy and colonial mediation. It demands that the postcolonial crisis be traced not merely to bad leadership or ethnic politics but to a longer history of underdevelopment, external extraction and local collaboration. To take Rodney seriously would mean rewriting Sierra Leone’s past from below and from the outside in at the same time. From below, because the labouring, captured, displaced, taxed, conscripted and governed would have to become central historical subjects. From the outside in, because Sierra Leone’s history cannot be understood apart from the Atlantic slave trade, European capitalism, imperial rivalry, colonial extraction and Third World struggles against domination. Rodney’s problematic was to hold these scales together. He could move from the local to the global without losing sight of either. The tragedy is that Sierra Leonean historiography has not fully developed this possibility. Rodney should have provoked a school. He should have forced generations of historians to ask how the ‘precolonial’ social formations of the Upper Guinea Coast shaped the later colonial order. He should have compelled scholars to revisit the relationship between the colony and the protectorate through older histories of trade, migration, warfare and social hierarchy. He should have inspired studies of labour, women, captives, artisans, traders, soldiers, secret societies, religious change and popular resistance within a broader political economy. He should have made it impossible to write Sierra Leonean history as a sequence of colonial episodes and postcolonial crises. Instead, his work remains like a buried foundation: load-bearing, but unseen. To recover Rodney is not to canonise him uncritically. His conclusions can and should be debated. Later scholarship may revise his interpretation of the Mani invasions, complicate his use of ethnic categories, expand the role of oral traditions, archaeology, gender, ecology, Islam and interior commercial networks. His Marxist framework can be questioned, sharpened or reworked. But meaningful engagement requires more than citation. It requires argument. It requires entering the terrain Rodney opened and asking whether his questions still illuminate the Sierra Leonean past. And they do. They illuminate the problem of origins: not the shallow origin of the colonial nation but the deeper making of peoples, polities and social relations. They illuminate the problem of power: how ruling groups emerge, how they control people, how they mediate commerce, how they adapt to external pressure. They illuminate the problem of exploitation: how labour is organised, how captives are turned into commodities, how wealth is accumulated, how violence becomes economic structure. They illuminate the problem of dependency: how external trade reshapes internal life long before formal colonial conquest. They illuminate the problem of liberation: how the struggle against underdevelopment must be historical as well as political. Rodney’s place in Sierra Leone historiography is therefore paradoxical. He is not marginal because his work lacks relevance. He is marginal because his relevance is too radical for the historiography that followed. He belongs at the centre, but he has been kept at the edge. He is the unclaimed ancestor of a Sierra Leonean historical tradition that has not yet fully come into being. To place Rodney properly is to say that the history of Sierra Leone must be written beyond the limits of colonial temporality, beyond the comfort of elite nationalism, beyond the administrative categories of empire, and beyond the narrowness of national exceptionalism. It must be written as part of Upper Guinea history, Atlantic history, African social history and the history of global capitalism. It must be written with attention to the people who bore the weight of those processes and to the structures that made their exploitation possible. Rodney’s great contribution was to show that Sierra Leone’s past was never small. It was never merely local. It was never simply colonial. It was part of the making of the modern world. And that is precisely why the refusal to engage with him matters. To neglect Rodney is to shrink Sierra Leone’s history. To recover him is to restore its scale, its conflict, its people and its unfinished emancipatory meaning.